2021
DOI: 10.5115/acb.21.101
|View full text |Cite
|
Sign up to set email alerts
|

Radiologic evaluation of congenital anomalies of anterior and posterior arch of atlas in Omani subjects

Abstract: The atlas (C1) is known to show congenital anomalies in its anterior and posterior arches. Though posterior arch anomalies are well known, the anterior arch anomalies are seldom reported in the literature [1]. Currarino et al. [1] have classified posterior arch anomalies into five types: Type A, failure of fusion of two hemi arches; Type B, defect in one side of the arch, Type C, defects on both sides of arch, Type D, absence of arch except posterior tubercle, and Type E, absence of whole arch including tuberc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…The prevalence of anatomical variations in at least one of the two arches of the atlas, as reported in previous literature, ranges between 0.074 and 5.16%, based on findings from both cadaveric and imaging studies (Senoglu et al, 2007;Hyun et al, 2018;Sanchis-Gimeno et al, 2018;Hinai et al, 2021). These statistics are in alignment with the results of the current study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The prevalence of anatomical variations in at least one of the two arches of the atlas, as reported in previous literature, ranges between 0.074 and 5.16%, based on findings from both cadaveric and imaging studies (Senoglu et al, 2007;Hyun et al, 2018;Sanchis-Gimeno et al, 2018;Hinai et al, 2021). These statistics are in alignment with the results of the current study.…”
Section: Discussionsupporting
confidence: 92%
“…The 7 included studies were published between 1986 and 2018, and conducted in Canada ( Piatt Jr and Grissom, 2011 ), China ( Choi et al, 2011 ), India ( Currarino et al, 1994 ), South Korea ( Geist et al, 2014 ; Kim, 2015 ), Turkey ( Hinai et al, 2021 ) and the United States of America ( Martirosyan et al, 2011 ), with a total of 8 patients. All of the included records were case reports.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite its low prevalence, atlas deformity associated with spinal cord compression constitutes a potentially devastating condition, which may lead to quadriplegia and even death (1,2). In 1989, Sawada et al (3) first reported the use of C1 laminectomy (C1L) for a case of canal stenosis at the level of the atlas.…”
Section: Introductionmentioning
confidence: 99%